2015
DOI: 10.1186/s12968-015-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cardiovascular magnetic resonance derived right ventricular function in patients with interstitial lung disease

Abstract: BackgroundCardiovascular magnetic resonance (CMR) provides non-invasive and more accurate assessment of right ventricular (RV) function in comparison to echocardiography. Recent study demonstrated that assessment of RV function by echocardiography was an independent predictor for mortality in patients with interstitial lung disease (ILD). The purpose of this study was to determine the prognostic significance of CMR derived RV ejection fraction (RVEF) in ILD patients.MethodsWe enrolled 76 patients with ILD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…death, HF, and pneumonia requiring hospitalization) in ILD patients with RV ejection fraction derived by cardiac magnetic resonance imaging (CMR) but not with TAPSE or RV fractional area change determined by echocardiography. Similar to the findings in that study [28], RV s 0 and TAPSE were also not selected as predictors of mortality in the present study ( Table 2). Taken together, the findings suggest that determination of RV systolic function by a more accurate and reproducible modality (e.g.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…death, HF, and pneumonia requiring hospitalization) in ILD patients with RV ejection fraction derived by cardiac magnetic resonance imaging (CMR) but not with TAPSE or RV fractional area change determined by echocardiography. Similar to the findings in that study [28], RV s 0 and TAPSE were also not selected as predictors of mortality in the present study ( Table 2). Taken together, the findings suggest that determination of RV systolic function by a more accurate and reproducible modality (e.g.…”
Section: Discussionsupporting
confidence: 86%
“…This low rate of RV dilation might account for the lack of predictive value of RV dilatation for mortality in the present study. Kato et al [28] recently demonstrated a significant association of hard events (e.g. death, HF, and pneumonia requiring hospitalization) in ILD patients with RV ejection fraction derived by cardiac magnetic resonance imaging (CMR) but not with TAPSE or RV fractional area change determined by echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of RV function remains problematic because of the chamber's complex anatomical features and the impact of loading and pressure conditions. Although magnetic resonance imaging (MRI) is known to be more accurate [19][20][21], echocardiography remains an indispensable, cost-effective, and practical imaging tool for assessment of RV systolic function [22]. Among the parameters used to assess RV function, FAC, TAPSE, and RV myocardial performance index are useful and reproducible measures of RV systolic function [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension was defined by right heart catheterization [211]. The median RVEF was lower in ILD patients with PH (43.1 %) compared to those without PH (53.8 %).…”
Section: Variamentioning
confidence: 99%